1994
DOI: 10.1063/1.112855
|View full text |Cite
|
Sign up to set email alerts
|

High-quality GaN heteroepitaxial films grown by metalorganic chemical vapor deposition

Abstract: We report the growth of high-quality GaN heteroepitaxial films on (0001) sapphire substrates by low-pressure metalorganic chemical vapor deposition. These films have exhibited narrow x-ray-diffraction rocking curves with full-width-at-half-maximum values as low as ΔΘ∼38 arc sec. These are the narrowest x-ray-diffraction rocking curve linewidths reported to date for any III-V nitride film. Electrical and optical measurements further indicate the samples to be of high quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…One film has significant broadening in the (00l) reflection consistent with a screw or mixed TD density of ϳ4ϫ10 8 film has a very narrow (00l) reflection similar to the results of Fertitta et al 11 and Kung et al 12 We show that for both materials the and 2-scan widths are broader for asymmetric (hkl) reflections compared to symmetric (00l) reflections. These results are in agreement with the specific defect structures measured by TEM.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…One film has significant broadening in the (00l) reflection consistent with a screw or mixed TD density of ϳ4ϫ10 8 film has a very narrow (00l) reflection similar to the results of Fertitta et al 11 and Kung et al 12 We show that for both materials the and 2-scan widths are broader for asymmetric (hkl) reflections compared to symmetric (00l) reflections. These results are in agreement with the specific defect structures measured by TEM.…”
supporting
confidence: 77%
“…10 These results suggest that the films are heavily dislocated. In contrast, other groups working on nitridebased semiconductors have reported rocking curves as narrow as 37 arcsec 11 and 30 arcsec. 12 The dislocation densities and dislocation structures in hexagonal GaN-based materials have also been measured directly by transmission electron microscopy ͑TEM͒.…”
mentioning
confidence: 84%
“…It can thus be concluded that the Al 2 O 3 -based buffered layer induced by thermal passivation shows higher thermal stability than that of the MgO-terminated revealed by x ray rocking curve (XRC) analysis, was 0.61 , larger than for GaN grown on sapphire. 37 The difference between them may be attributable to the different deposition and processing methods employed. To improve the quality of GaN on MgAl 2 O 4 substrate, optimization of deposition and processing is still underway.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness of a buffer layer plays a very important role in growing a good epitaxial film. 2 To understand the importance of the GaN buffer layer, detailed thin-film structure related with the electronic properties should be studied as functions of buffer thickness. However, in the past, most of the GaN films measured with x-ray diffraction method mainly reported the rocking curve of the diffraction peak in the plane-normal direction.…”
mentioning
confidence: 99%